Mourning Rituals in Archaic & Classical Greece and Pre-Qin China - Wu, Xiaoqun (Springer Singapore, 2018)
This pivot compares mourning rituals in Archaic & Classical Greece and Pre-Qin China to illustrate some of the principles and methods used in comparative studies. It focuses on three main aspects of mourning of the dead before burial - lamentation, mourners' gestures and behaviors, and mourning apparel-to demonstrate the cultural function, purpose, and social influence of mourning. A key comparative study of rituals at the heart of both Western and Chinese culture, this text highlights the cultural function and social influence of rituals of two ancient peoples and will be of interest to all scholars of comparative religion, sociology and anthropology.